PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI TAMAN NASIONAL BUKIT TIGAPULUH DESA RANTAU LANGSAT KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Alpian Munandar; Defri Yoza; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
National Park Bukit Tigapuluh is an area with one of the goals stipulation that as the development of tourism.Exploiting this potential is real necessary human resources, capital, appropriate technology and management wise order not to cause a negative environmental impact and socio-cultural area surrounding communities. Utilization of this course should stick to the principles of conservation, education, economy, recreation and community participation.Society has a role in the development of ecotourism and to be seen how far the future benefits the surrounding community. Ecotourism development with the involvement of local communities is relatively easy to implement because the local people have the opportunity to develop the tourist objects in the surrounding areas and provide greater opportunities also in the local community participation in decision-making. The purpose of this study was to identify the potential for ecotourism in the village of RantauLangsat, knowing the perceptions, interests and community participation in the development of community-based ecotourism and strategy to develop community-based ecotourism. Methods of data collection is done by surveys and community-based ecotourism using SWOT method. The results showed that some of the ecotourism potential of natural and cultural tourism ecotourism local communities. some of the development strategy of community-based ecotourism should be applied, namely the incorporation of the potential of nature and culture of RantauLangsat to attract visitors, enhance the capacity of the HR community through the provision of a wide range of technical training, procurement of repair facilities and infrastructure to meet customer satisfaction, training in the management of financial management good for the management of ecotourism in RantauLangsat and Attracting investors to smooth travel management in RantauLangsat.keywords:National Park ,Ecotourism, Community Based, Development